Low noise amplifier design with enhanced noise and gain performance using transformer boosting method for millimeter‐wave applications. Issue 9 (6th May 2022) - Agarwal, Nitin; Gupta, Manish; Kumar, Manish
Abstract: In low noise amplifier (LNA) design, achieving minimum noise figure (NF) and enhanced gain is equally important in the field of communication. The major aim of this design with previous methods are those having implemented in the topology of design like metal oxide semiconductor field effect transistor at common source connection topology, pole‐based transformer boosting, and dual feedback technique. However, these methods fail to reach the desired performance due to their low NF and low gain. In order to overcome these failures and their causes, this article presented a topology in LNA design using a transformer as boosting component to improve the performance of NF and gain for millimeter‐wave applications. It has three common gate stages connected in cascode form, and three transformers are acquired to link the drain to the input signal. Transformers permit radio frequency feeding signal from drain to source, and output from the previous stage is connected to the input of the next stage. This connection increases the gain of the circuit and an enlarged coupling coefficient of value "1, " which minimizes noise. The unilateral coefficient remains to be 1, to make the circuit stable throughout execution. NF value can be minimized by properly selecting conductance coefficient and S ‐parameter values. Since the transformer is used to provide feedback in this circuit, stability condition has to be analyzed carefully. Output load value is selected optimum as it creates an impact on the stability of LNA. This topology implemented in LNA design helps to increase the gain by boosting the signal input, and hence, in turn, it increases overall gain performance. Similarly, while executing this optimal LNA design using transformer boosting technique in CADENCE software, this LNA exhibits a minimum NF of 3 dB at 30 GHz and power gain of 12.2 dB at 50 GHz in measurement. Comparatively, the proposed LNA design overruns conventional methods and consumes a power supply of 1.1 V. Abstract : The proposed low noise amplifier (LNA) design consists of N‐channel metal oxide semiconductor field effect transistor (MOSFET) connected with a transformer feedback circuit. Here resistors and inductors are neglected using a transformer, and it shows a coupled circuit design. LNA is designed as a three‐stage amplifier by two radio frequency (RF) components powered with a current source to enhance performance. The circuit is driven with RF activated power source, and output is gathered as RF and millimeter‐wave as dB values. Effective susceptance was measured across metal oxide semiconductor field effect transistor (MOSFET), then it is estimated for a low NF value. In a communication system, the receiver is a very critical block and responsible for recovering transmitted data from an obtained weak signal. The obtained signal consists of interference and noise. The optimal receiver should retain high gain value and low NF that helps to restore the low power of the received signal with low minimal noise added. The proposed LNA design is optimized for communication by using a transformer boosting model to enrich the voltage source, and in turn, it increased gain.